Production of Extra Cellular Exoglucanase by Rhizopus oryzae from Submerged Fermentation of Agro Wastes - Rina Rani Ray, Soumita Mukherjee, Moumita Karmakar and (Recent Research in Science and Technology, 2011)
Rhizopus oryzae PR7 MTCC 9642, a producer of endoglucanse was found to produce extra cellular exoglucanase or avicelase when grown on avicel or micro crystalline cellulose. In order to curtail the cost of production the strain was grown in media supplemented with various cellulosic wastes, of which dried flower showed the best result followed by the sweet lime peel at optimum pH 8.0 and 5.0 respectively at 37° C. Peptone was found to be the best nitrogen source for exoglucanase production whereas amongst metal ions Mn2+ and Fe2+ could bring a 1.23 fold increase in enzyme production in sweet lime peel supplemented culture. Under optimized condition, highest exoglucanse production was achieved at 96 hours of growth. The enzyme showed optimum activity at pH 5.0 and 40°C and stability at pH range of 5-9 and about 90% activity was retained even after an exposure of 10 minutes at 80° C. The enzyme activity was enhanced in presence of Mn2+ and Fe2. The enzyme was found to saccharify avicel and the wastes into cellobiose.